The effect of telang flower extract on kidney function and histopathological features of obese rat kidneys - Astuti, Mia Puji; Lister, Clarissa; Renaldi, Muhammad Rizal; Suhartina, Suhartina (Jurnal Prima Medika Sains, 2024)
This study aims to determine the effect of oral administration of telang flower extract in several doses on histopathological changes in kidney organs. This study used a post test only control group design. Researchers used 6 Wistar rats for each experimental group, so that the total number of test animals in this study was 24. Grouping of test animals was done randomly into 4 test groups. Histopathological observations of kidney tissue were made by comparing the control and treatment groups. Changes observed will be the presence of fatty degeneration (vacuolization), necrosis and hydrophic degeneration. To obtain quantitative data, scoring was performed on each change found. The data from the study were then analyzed with the help of SPSS. Data normality test was analyzed by Kolmogorov-Smirnov test (p > 0.05). To test the significance between test groups, one-way analysis of variance or One Way ANOVA technique was conducted at 95% confidence level (p < 0.05). Further analysis or test was conducted using Post Hoc Test with LSD technique. The results showed that the administration of telang flower extract at a dose of 600mg/KgBB was effective in improving kidney function in obese Wistar white rats. This improvement is seen through increased levels of ureum, creatinine, and improved renal histological structure. Histopathological observation of kidney tissue showed that treatment group 3, which received telang flower extract at a dose of 600mg/KgBB, experienced significant improvement and was closer to the control group than the other groups.